Eddy-induced transport of the Kuroshio warm water around the Ryukyu Islands in the East China Sea. (1st July 2017) - Kamidaira, Yuki; Uchiyama, Yusuke; Mitarai, Satoshi
Abstract: In this study, an oceanic downscaling model in a double-nested configuration was used to investigate the role played by the Kuroshio warm current in preserving and maintaining biological diversity in the coral coasts around the Ryukyu Islands (Japan). A comparison of the modeled data demonstrated that the innermost submesoscale eddy-resolving model successfully reproduced the synoptic and mesoscale oceanic structures even without data assimilation. The Kuroshio flows on the shelf break of the East China Sea approximately 150–200 km from the islands; therefore, eddy-induced transient processes are essential to the lateral transport of material within the strip between the Kuroshio and the islands. The model indicated an evident predominance of submesoscale anticyclonic eddies over cyclonic eddies near the surface of this strip. An energy conversion analysis relevant to the eddy-generation mechanisms revealed that a combination of both the shear instability due to the Kuroshio and the topography and baroclinic instability around the Kuroshio front jointly provoke these near-surface anticyclonic eddies, as well as the subsurface cyclonic eddies that are shed around the shelf break. Both surface and subsurface eddies fit within the submesoscale, and they are energized more as the grid resolution of the model is increased. An eddy heat flux (EHF) analysis was performed with decomposition into the divergent (dEHF) and rotational (rEHF) components. The rEHF vectors appeared along the temperature variance contours by following the Kuroshio, whereas the dEHF properly measured the transverse transport normal to the Kuroshio's path. The diagnostic EHF analysis demonstrated that an asymmetric dEHF occurs within the surface mixed layer, which promotes eastward transport toward the islands. Conversely, below the mixed layer, a negative dEHF tongue is formed that promotes the subsurface westward warm water transport. Highlights: Oceanic simulation is conducted for the area around the Ryukyu Islands in ECS. Topographic shear and baroclinic instability enhance submesoscale eddies in ECS. Submesoscale eddies promote lateral material transport from Kuroshio.